2015
DOI: 10.2147/dddt.s82263
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/antioxidant status, paraoxonase activity, and lipid profile in plasma of ovariectomized rats under the influence of estrogen, estrogen combined with progesterone, and genistein

Abstract: IntroductionThe aim of this study was to investigate whether estradiol (E2), E2 combined with progesterone (Prog) (E2/Prog), and genistein (Gen) treatment had antioxidative and anti-hyperlipidemic effects in the plasma of ovariectomized (OVX) rats.Materials and methodsAdult female Sprague–Dawley rats were divided into five groups. Rats in all groups, except for those in a sham group, underwent bilateral ovariectomy under general anesthesia. The groups were as follows: sham group; control OVX group; group treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Also, production of estrogen and testosterone depend on high LH secretion. It has been indicated that estrogen has significant antioxidant effects at high concentrations (21)(22)(23)(24). Levels of LH and FSH were reduced significantly in rats after six weeks of exposure to ELF-EMF of 50 Hz and 25 μT.…”
Section: Results Of Estrogen Levels Measurementmentioning
confidence: 99%
“…Also, production of estrogen and testosterone depend on high LH secretion. It has been indicated that estrogen has significant antioxidant effects at high concentrations (21)(22)(23)(24). Levels of LH and FSH were reduced significantly in rats after six weeks of exposure to ELF-EMF of 50 Hz and 25 μT.…”
Section: Results Of Estrogen Levels Measurementmentioning
confidence: 99%
“…Estrogen has been shown to enhance PON1 activity via the ER in vitro, but without altering PON1 mRNA levels or protein concentrations (132). Daily oral administration of genistein (10 mg/kg body weight) for 8 wk did not alter HDL cholesterol or serum paraoxonase activity in ovariectomized SpragueDawley rats (133). In contrast, in female Sprague-Dawley rats with collagen-induced arthritis, daily oral administration of genistein (20 mg/kg body weight) or daidzein (20 mg/kg body weight) for 50 d significantly improved serum PON1 paraoxonase and arylesterase activities, but did not alter HDL cholesterol (134).…”
Section: Isoflavonesmentioning
confidence: 97%
“…The OVX 1 E2 group were given a 17b-E2 (0.25 mL/kg/d, 10 lg/0.1 mL) supplement 16 1 month after the bilateral OVX. The OVX 1 P group were given a progesterone (0.3 mL/kg/d, 10 mg/ 1 mL) supplement 17 1 month after bilateral OVX. The OVX 1 E2 1 P group were given E2 and P supplements 1 month after the bilateral OVX.…”
Section: Ovariectomy and Hormone Replacement Therapymentioning
confidence: 99%